T Cell Transfection: Coming in and Finding Out: Blending Receptor‐Targeted Delivery and Efficient Endosomal Escape in a Novel Bio‐Responsive siRNA Delivery System for Gene Knockdown in Pulmonary T Cells (Adv. Therap. 7/2019). Issue 7 (8th July 2019) - Kandil, Rima; Xie, Yuran; Heermann, Ralf; Isert, Lorenz; Jung, Kirsten; Mehta, Aditi; Merkel, Olivia M.
Abstract : T cells are notoriously difficult to transfect. In article number1900047, Olivia M. Merkel and co‐workers describe a polymeric nanoparticle system for siRNA delivery that is decorated with transferrin, which interacts with the transferrin receptor found upregulated on activated T cells and with pH‐responsively protected melittin, which mediates endosomal escape upon deprotection in the acidic environment of the endo‐lysosome for efficient gene silencing in T cells.